PENGARUH CONTENT MARKETING, ONLINE CONSUMER REVIEW DAN BEAUTY VLOGGER TERHADAP KEPUTUSAN PEMBELIAN ONLINE PRODUK HIJAB RABBANI PADA GENERASI Z DI KOTA SEMARANG - Fajar Adhitya (EKOBIS, 2022)
This study aims to analyze the effect of content marketing variables, online consumer reviews and beauty vloggers on purchasing decisions for Rabbani hijab products through the Shopee application. This research is a type of quantitative research with a descriptive approach. The population is taken from Generation Z who live in Semarang City who have bought Rabbani hijab products through the Shopee application. The sample of this research is 100. The technique used in sampling is probability sampling technique using simple random sampling method. data collection is done by distributing questionnaires and documentation. Then the data analysis technique uses multiple linear regression analysis while for data processing using the IBM SPSS Statistics version 24 program. The results of the analysis show that: 1) content marketing has a significant influence on purchasing decisions, 2) online consumer reviews have a significant influence on purchasing decisions, 3 ) beauty vlogger has a significant influence on purchasing decisions.